PARENTING SEBAGAI BASIS PENDIDIKAN KARAKTER BERSAMA PADA LEMBAGA TPQ AL HIDAYAH GRASAK GONDANG SRAGEN - Sumarno Sumarno (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
This community service program aimed to improve parents' understanding and skills in implementing character-based parenting through a parenting education program at TPQ Al Hidayah Grasak Gondang in 2026. The program employed a Participatory Action Research (PAR) approach consisting of needs assessment, material preparation, parenting seminars, interactive discussions, family mentoring, monitoring, and evaluation. Participants included parents, Qur'anic teachers, TPQ administrators, and community leaders. The results indicate that the parenting program successfully enhanced parents' understanding of exemplary behavior, positive communication, religious habituation, discipline, and collaboration between families and TPQ in strengthening children's character. Furthermore, the program fostered stronger cooperation between parents and TPQ administrators in supporting children's moral development. Overall, the program contributed positively to establishing a sustainable character education culture both at home and within the TPQ environment